2020
DOI: 10.1016/j.wem.2020.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Review of Scorpion Stings and Snakebites Treated by the French Military Health Service During Overseas Operations Between 2015 and 2017

Abstract: IntroductiondDepending on their theatre of operation, French soldiers may potentially be exposed to scorpion stings and snakebites. Following the recommendations of a French military health service (FMHS) technical committee for envenomation, the FMHS provides antivenoms appropriate to each deployment. This work aimed to evaluate this risk of envenomation and to assess the antivenoms used by the FMHS in operational theatres since the creation of this committee in 2015.MethodsdCases were identified based on a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The use of this antivenom was associate with a decrease in envenoming clinical signs in patients who received prompt and specific antivenoms [ 204 ]. Additionally, a study by the French military demonstrated that 19 patients were effectively treated with SCORPIFAV (MicroPharm) [ 205 ]. There also exists some preclinical data indicating the potential usefulness of antivenoms in treating scorpionism for Polyvalent Scorpion Antivenom (Razi) [ 206 – 209 ], Purified polyvalent anti-scorpion serum (VACSERA) [ 210 ], Inoscorpi (Inosan Biopharma) [ 211 ].…”
Section: Treatment Of Severe Animal Envenomings In the Mena Regionmentioning
confidence: 99%
“…The use of this antivenom was associate with a decrease in envenoming clinical signs in patients who received prompt and specific antivenoms [ 204 ]. Additionally, a study by the French military demonstrated that 19 patients were effectively treated with SCORPIFAV (MicroPharm) [ 205 ]. There also exists some preclinical data indicating the potential usefulness of antivenoms in treating scorpionism for Polyvalent Scorpion Antivenom (Razi) [ 206 – 209 ], Purified polyvalent anti-scorpion serum (VACSERA) [ 210 ], Inoscorpi (Inosan Biopharma) [ 211 ].…”
Section: Treatment Of Severe Animal Envenomings In the Mena Regionmentioning
confidence: 99%